Regulating and Supervising Fintech in Brazil: Insights from the Central Bank Experience and Emerging Challenges - Almeida Paolinelli de Castro, Flávio (Iuris Dictio, 2025)
Brazil’s rapidly expanding fintech sector has led the Central Bank of Brazil (BCB) to implement an adaptive regulatory approach. This article analyzes how the BCB has addressed the challenges of fintech growth by modernizing regulation and strengthening its risk-based supervisory framework. The findings indicate that proportional, principles-based, and adaptive regulation, combined with innovative initiatives, can enhance financial inclusion while preserving stability and consumer protection. However, the experience also reveals ongoing challenges, including emerging risks and capacity constraints. The Brazilian case offers analytical insights for other emerging economies seeking to balance innovation, inclusion, and financial stability within a coherent regulatory and supervisory framework.